2021
DOI: 10.21203/rs.3.rs-806304/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Genetic propensity for obesity, socioeconomic position, and trajectories of body mass index in older adults

Abstract: Background Identifying how socioeconomic positioning and genetic factors interact in the development of obesity is imperative for population-level obesity prevention strategies. The current study investigated whether social positioning, either independently or through interaction with a polygenic score for Body Mass Index (BMI-PGS), influences BMI trajectories across older adulthood. Methods Data were analysed from 7,183 individuals from the English Longitudinal Study of Aging (ELSA). Interactions between th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 25 publications
0
2
0
Order By: Relevance
“…Second, it is unclear how genetic and socioeconomic position (SEP) [ 15 17 ] influences on BMI operate together. It has been suggested that there may be multiplicative effects [ 18 20 ], such that genetic influences are largest amongst those in disadvantaged SEP whom have fewer resources available to protect against weight gain or to initiate/maintain weight loss [ 18 , 19 ]. While this is a compelling narrative, evidence for this suggestion is equivocal, with some studies reporting weak [ 19 ] or mixed [ 18 ] results.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Second, it is unclear how genetic and socioeconomic position (SEP) [ 15 17 ] influences on BMI operate together. It has been suggested that there may be multiplicative effects [ 18 20 ], such that genetic influences are largest amongst those in disadvantaged SEP whom have fewer resources available to protect against weight gain or to initiate/maintain weight loss [ 18 , 19 ]. While this is a compelling narrative, evidence for this suggestion is equivocal, with some studies reporting weak [ 19 ] or mixed [ 18 ] results.…”
Section: Introductionmentioning
confidence: 99%
“…It has been suggested that there may be multiplicative effects [ 18 20 ], such that genetic influences are largest amongst those in disadvantaged SEP whom have fewer resources available to protect against weight gain or to initiate/maintain weight loss [ 18 , 19 ]. While this is a compelling narrative, evidence for this suggestion is equivocal, with some studies reporting weak [ 19 ] or mixed [ 18 ] results. Further, lack of replication in early gene x environment interaction studies [ 21 ] suggests that publication bias could have occurred.…”
Section: Introductionmentioning
confidence: 99%